Estructura de la industria manufacturera según el valor de ventas - Cárdenas Núñez, Gilberto José Rafael (2010)
After many years there is an economic census in Peru, with the effect of having again specialized information on the manufacturing productive economic sector. The analysis shows that the manufacturing structure is specially designed for the domestic market, and with minimal development of the capital goods sector. A manufacturing sector that put to Peru as a producer of non-tradable manufactured goods even though many governments have signed several FTA s with several countries or economic groups in the world. Peruvian manufacture sector in simple and typical of extremely backward countries in the production of goods with some degree of technological development.